Maternal outcomes among emergency obstetric admissions at a tertiary care teaching hospital in Chitradurga, South India - Arpana, Anju; B. M., Rashmi; V., Latha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The maternal mortality is a vital index of the quality and efficiency of obstetric services prevailing in a country. The obstetric emergencies are unexpected occurrences during pregnancy or puerperium requiring immediate attention. Obstetric emergencies can either happen suddenly or they can develop as a result of complications that are not properly identified, monitored or managed. These emergencies, to a large extent, are preventable. The purpose of this study was to understand the contributing factors of obstetric emergencies, their clinical presentation, management and maternal outcomes. Methods: A cross sectional study was conducted among obstetric emergency admissions during October 2016 to September 2017, at a tertiary care hospital in urban area of central Karnataka. Results: A total of 100 emergency admissions were observed in the study period. A 41% of were un-booked antenatal cases. A 13% of patients reached with the longest delay of 10-12 hours duration. A 31% of emergency admissions were in compromised condition. The majority of the cases were delivered by LSCS (55%). Conclusions: In the study, nearly half of the pregnancies were unbooked. There were teenage pregnancies reported in the study. More than half of obstetric emergencies were from rural areas. In nearly 50% of admissions a delay of more than 5 hours in reaching this hospital was noted. Ignorance was a major factor which impeded the access of antenatal health care services. Health education to pregnant women about importance of accessing maternal health services, early ANC booking and regular checkups, identification of high-risk pregnancy and timely referral, availability of fully functional first referral units and transport facilities for these emergency patients. Availability of skilled medical professionals round the clock in these FRU’s are the need of the hour.